Interrogating the CD27:CD70 axis in αCD40-dependent control of pancreatic adenocarcinoma - Gamache, Awndre; Conarroe, Claire; Adair, Sara; Bauer, Todd; Padilla, Frederic; Bullock, Timothy N. J. (Frontiers in Cell and Developmental Biology, 2023)
Immune checkpoint blockade immunotherapy has radically changed patient outcomes in multiple cancer types. Pancreatic cancer is one of the notable exceptions, being protected from immunotherapy by a variety of mechanisms, including the presence of a dense stroma and immunosuppressive myeloid cells. Previous studies have demonstrated that CD40 stimulation can remodel the tumor microenvironment in a manner that promotes effector immune cell responses and can cooperate with immune checkpoint inhibition for durable tumor control mediated by T cells. Here we confirm the capability of this combination therapy to dramatically, and durably, control pancreatic cancer growth in an orthotopic model and that the immune memory to this cancer is primarily a function of CD4+ T cells. We extend this understanding by demonstrating that recruitment of recently primed T cells from the draining lymph nodes is not necessary for the observed control, suggesting that the pre-existing intra-tumoral cells respond to the combination therapy. Further, we find that the efficacy of CD40 stimulation is not dependent upon CD70, which is commonly induced on dendritic cells in response to CD40 agonism. Finally, we find that directly targeting the receptor for CD70, CD27, in combination with the TLR3 agonist polyIC, provides some protection despite failing to increase the frequency of interferon gamma-secreting T cells.